Unsettling Trends in Collective Bargaining Today - Raluca Dimitriu (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Today, there is virtually no legal system that does not enshrine collective bargaining – as the foundation of a balance of forces in the labour market. At each level it is conducted (international - European - national - sector - local - unit), it determines the way labour relations are regulated and gives workers the opportunity to express themselves, through solidarity, with a unique voice. Through collective bargaining, employees have the opportunity, by uniting their bargaining power to counter-balance the superior power of the employer, to determine the acceptance of (some of) the demands and the contractual regulation of fair wages and working conditions, in relation to the possibilities and needs of each party. Currently, one cannot but notice that collective bargaining has indeed its limits, some circumstantial, others permanent. Collective bargaining takes place increasingly more timid and in rather marginal areas, its results covering a smaller number of employees. As traditional expression of the solidarity between workers, collective bargaining – while this solidarity displays signs of dissolution – has diminished its strength and shows a centrifugal, decentralising tendency.The paper presents some of the circumstances that can be considered responsible for the tendency to compress collective bargaining at all levels. Certain causes are therefore analyzed: globalization, detailed legalization, the competitive relationship between employees, the consumers' pressure or the opposition of the individual employee.
Keywords: K31; 650; Labour law; collective bargaining; European Union; collective agreement